2021
DOI: 10.1038/s41467-021-21177-5
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic loss of BCMA as a resistance mechanism to CAR T cell therapy in a patient with multiple myeloma

Abstract: BCMA targeting chimeric antigen receptor (CAR) T cell therapy has shown deep and durable responses in multiple myeloma. However, relapse following therapy is frequently observed, and mechanisms of resistance remain ill-defined. Here, we perform single cell genomic characterization of longitudinal samples from a patient who relapsed after initial CAR T cell treatment with lack of response to retreatment. We report selection, following initial CAR T cell infusion, of a clone with biallelic loss of BCMA acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
143
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(169 citation statements)
references
References 31 publications
(36 reference statements)
2
143
0
Order By: Relevance
“…Specifically, it has been observed that for BCMA-targeting agents, antigen deregulation could happen as a consequence of previous anti-BCMA treatments (e.g., belantamab) or by genetic alterations. Indeed, biallelic loss of BCMA has been reported in several patients relapsing after anti-BCMA CAR-T [80,81]. Additionally, after a deeper analysis, a heterozygous TNFRSF17 loss or monosomy of 16 in about 15% of MM patients never exposed to anti-BCMA therapy has been observed, letting us hypothesize a role for genomic alteration in the development of resistance to BCMAtargeting treatments [80,81].…”
Section: Long-term Failure Of Novel Immunotherapies: Pitfalls and Opportunitiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Specifically, it has been observed that for BCMA-targeting agents, antigen deregulation could happen as a consequence of previous anti-BCMA treatments (e.g., belantamab) or by genetic alterations. Indeed, biallelic loss of BCMA has been reported in several patients relapsing after anti-BCMA CAR-T [80,81]. Additionally, after a deeper analysis, a heterozygous TNFRSF17 loss or monosomy of 16 in about 15% of MM patients never exposed to anti-BCMA therapy has been observed, letting us hypothesize a role for genomic alteration in the development of resistance to BCMAtargeting treatments [80,81].…”
Section: Long-term Failure Of Novel Immunotherapies: Pitfalls and Opportunitiesmentioning
confidence: 92%
“…Indeed, biallelic loss of BCMA has been reported in several patients relapsing after anti-BCMA CAR-T [80,81]. Additionally, after a deeper analysis, a heterozygous TNFRSF17 loss or monosomy of 16 in about 15% of MM patients never exposed to anti-BCMA therapy has been observed, letting us hypothesize a role for genomic alteration in the development of resistance to BCMAtargeting treatments [80,81]. On the other hand, the activity of anti-CD3/BCMA bispecific antibodies have been found to be completely abrogated by the presence of granulocyte-like MDSC [16] or dysfunctional/exhausted T-cells, which arise under an immunosuppressive microenvironment characterized by a repeated T-cell stimulation [79].…”
Section: Long-term Failure Of Novel Immunotherapies: Pitfalls and Opportunitiesmentioning
confidence: 99%
“…The mechanism whereby BCMA CAR T cells reduce BCMA cell-surface expression levels probably includes selection of cells with lower BCMA levels, whereas tumor cells with higher BCMA expression are eliminated. Furthermore, biallelic BCMA deletions, resulting in lack of BCMA expression, have also recently been found to trigger resistance to BCMA CAR T cells (27)(28)(29). Although BCMA antigen loss seems to be an uncommon mechanism of escape from BCMA-directed CAR T-cell therapy (4% in the KarMMa study; ref.…”
Section: Tumor-related Resistance Mechanisms (Soluble) Bcmamentioning
confidence: 99%
“…Although BCMA antigen loss seems to be an uncommon mechanism of escape from BCMA-directed CAR T-cell therapy (4% in the KarMMa study; ref. 10), it may have major therapeutic implications because biallelic loss of BCMA will also confer resistance to retreatment with similar or other BCMA-targeted therapies (28). This highlights the need to examine for BCMA gene alterations or to assess BCMA expression when treatment with another BCMA-directed immunotherapy is considered.…”
Section: Tumor-related Resistance Mechanisms (Soluble) Bcmamentioning
confidence: 99%
“…61 A similar case of homozygous loss of BCMA expression has been reported in a patient in the phase I CRB-401 trial who was unsuccessfully treated at relapse, 9 months after the first infusion. 62 Although homozygous loss of BCMA genes is extremely rare, the 16p monosomy, leading to a heterozygous BCMA-deficient phenotype is relatively common and it has been suggested that it may be a mechanism leading to resistance to anti-BCMA therapies. 61 At the time of analysis, OS was immature, with 66% of patients still censored, 78% of patients were alive at 12 months, and the estimated median OS was 19.4 months [95% confidence interval (CI), 18.2–non-evaluable].…”
Section: Idecabtagene Vicleucel Developmentmentioning
confidence: 99%